Data standardization management method and system for medical big data - WANG RONG; JIAN YIPENG; HU DANDAN; GAO SHAN (2023)
The invention relates to the technical field of data management, in particular to a data standardization management method and system for medical big data. Comprising the following steps: S100, acquiring various types of original medical data from a data source through different data acquisition modes, and storing the original medical data into a medical original database; s200, performing standardization processing on the original medical data to obtain standard medical data, and storing the standard medical data to a medical standard database; s300, determining medical subject objects and associated dimensions thereof, generating a medical subject object table, calling standard medical data of the associated dimensions of the medical subject objects from the medical standard database, and filling the standard medical data into the medical subject object table; and S400, acquiring a medical thematic scene of the data service, generating a medical thematic table, determining a medical subject object needing t